(untitled) (AYUSHDHARA, 2023)
Ayurveda is the oldest scientific systems of medicine. Shalakya Tantra is one of the branches of Ashtanga Ayurveda which deals with the diseases arise above the clavicle region. This stream of Astanga Ayurveda mainly comprises of etiology, histopathology, symptomatology and treatment in the form of local and systemic administration related to eyes, nose, ears and mouth etc. Kriyakalpa is the treatment method usually adopted in Netra Vikaras. Netra Tarpana is one among the Kriyakalpas which is advised in many Netra rogas to normalize the vitiated Doshas. Akshi Tarpana splits into two words “Akshi” means eye and “Tarpana” means nourishment. Tarpana is a Snigdha Kriya indicated in Vata Dusta ophthalmic conditions mainly in Dristigata Rogas. It is commonly indicated in macular degeneration, computer eye strain, degenerative conditions, myasthenia gravis, drooping of eyelid. The therapeutic effect is advocated for patients suffering from diseases of eye. In healthy people Eye Care Treatment is carried out to protect the eyes from degeneration due to ageing process and to improve the eye sight. Thus Akshi Tarpana is an excellent soothing, relaxing eye treatment to rejuvenate eyes and surrounding tissues. This Review study was performed with the aim to study the concept of Akshi Tarpana, understand the standard procedure of Akshi Tarpana and its efficacy.